Relative age effect among elite youth female soccer players across the United States - Korgaokar, A. D.; Farley, R. S.; Fuller, D. K.; Caputo, J. L. (SportMont, 2018)
The consequence of relative age effect (RAE) has been an overrepresentation of athletes born early in the cohort and an underrepresentation of athletes born late in the cohort. There are significantly fewer studies that examine this phenomenon among female soccer players. Therefore, the purpose was to determine the existence of RAEs among elite youth female soccer players competing in the Elite Clubs National League (ECNL) during the 2012-2013 season. Player birthdates (U14-U18 N=7,294) were collected from the ECNL and compared to the birthdates distribution for the general population. Data revealed a RAE across all age groups (U14-U18) indicating a preference for the selection of the oldest in the cohort. An overrepresentation of players was observed in Q1 and an underrepresentation of players in Q4 among the U14-U17 age groups. Among the u18 age group, an overrepresentation of players was detected in Q2 and an underrepresentation of players in Q4. The birthdate distribution for the first and second halves of the playing season showed strong RAEs among the U14-U17 age groups. No statistically significant difference was found between the first and second halves of the playing season among players in the U18 age group.